Do elevated autoantibodies in patients with multiple sclerosis matter?. (3rd December 2018) - Dal‐Bianco, Assunta; Wenhoda, Fritz; Rommer, Paulus Stefan; Weber, Michael; Altmann, Patrick; Kraus, Jörg; Leutmezer, Fritz; Salhofer‐Polanyi, Sabine
Abstract : Objectives: The incidence and clinical impact of serum autoantibodies in patients with multiple sclerosis (MS) are controversially discussed. The aim of the study was to reassess the value of elevated serum autoantibodies in our MS study cohort. Material & Methods: In total, 176 MS patients were retrospectively analyzed for coexistence and clinical impact of increased serum autoantibody levels. Results: The 18.8% of the MS cohort showed elevated serum autoantibody levels, but only 10.2% of all MS patients were diagnosed with a further autoimmune disease (AI). Patients with elevated serum autoantibodies (AABS) were not significantly more often diagnosed with a clinical manifest AI as compared to patients with negative autoantibodies ( P = 0.338). MS patients with disease duration of more than 10 years showed no significant increase of positive autoantibodies as compared to patients with a more recent disease onset ( P = 1). MS patients with elevated serum autoantibodies did not exhibit a significantly worse disease course ( P = 0.428). Conclusions: According to our data, elevated serum autoantibodies do not have the potential to serve as a prognostic tool for disease severity in patients with MS Since MS patients with positive serum AABS did not significantly more often suffer from clinical manifest AIs than MS patients with negative serum AABS, the role of routine testing of serum AABS in MS patients should be critically called into question.